PENGARUH CURRENT RATIO (CR) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP KINERJA ASET PADA PT CHANDRA ASRI PACIFIC TBK TAHUN 2015-2024 - Triani, Dalis; Nurwita, Nurwita (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effect of Current Ratio (CR) and Total Asset Turnover (TATO) on asset performance, as measured by Return on Assets (ROA), at PT Chandra Asri Pacific Tbk during the 2015–2024 period. The research uses a quantitative approach with multiple linear regression analysis, supported by classical assumption tests and hypothesis testing (t-test, F-test, and coefficient of determination). Data processing was carried out using SPSS version 25 with secondary data obtained from the company’s annual financial reports. The t-test results show that partially, CR has no significant effect on ROA, as indicated by a t-value of 1,931 < the t-table value of 2,36462, and a significance level of 0,095 < 0,05. In contrast, TATO has a significant effect on ROA, with a t-value of 4,812 exceeding the t-table and a significance level of 0,002, which is below 0.05. Simultaneously, CR and TATO significantly affect ROA, supported by an F-value of 12,722, which is greater than the F-table value of 4,737, and a significance level of 0,005. The coefficient of determination (R²) is 0,784, indicating that 78,4% of the variation in ROA is explained by CR and TATO, while the remaining 21,6% is influenced by other variables. These findings suggest that asset efficiency (TATO) plays a more critical role in enhancing profitability than short-term liquidity (CR).